2015
DOI: 10.1002/app.42264
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and rheological properties of polypropylene/bentonite composites with stearic acid as an interface modifier

Abstract: In this study, we present a study of polypropylene/bentonite composites where stearic acid was used as both a surface and interface modifier during the compounding of composites. The concentration of bentonite was 1.5, 2.5, 5.0, and 10 parts per hundred. The composites were characterized by impact resistance and tensile tests, rheological analysis, the dispersion state of the filler observed by optical microscopy, and interaction between bentonite and stearic acid, as analyzed by Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…The enhancement of lubricity through the processing provided fine dispersion of the filler, and it was also in accord with the decrease in dimension and quantity of agglomerates showed by the SEM. This was in agreement with the findings of the authors of [23], who reported that during the processing of the PP/modified bentonite composites, the stearic acid is acting as an interface modifier and lubricant and thus decreases the viscosity of the melt compound due to the free movement of the polymer chains. These effects enhanced the mechanical behavior by improving the elongation at break of the composite.…”
Section: A Processability (Torque Value)supporting
confidence: 93%
See 2 more Smart Citations
“…The enhancement of lubricity through the processing provided fine dispersion of the filler, and it was also in accord with the decrease in dimension and quantity of agglomerates showed by the SEM. This was in agreement with the findings of the authors of [23], who reported that during the processing of the PP/modified bentonite composites, the stearic acid is acting as an interface modifier and lubricant and thus decreases the viscosity of the melt compound due to the free movement of the polymer chains. These effects enhanced the mechanical behavior by improving the elongation at break of the composite.…”
Section: A Processability (Torque Value)supporting
confidence: 93%
“…However, HDPE compatibilized with ethylene-acrylic acid copolymer (EAA) leads to poor dispersion due to its immiscibility with the HDPE matrix. Recently, authors in [23] confirmed that the composites containing modified bentonite in presence of stearic acid used as interface modifier induce a better dispersion of the filler, a decrease in viscosity and an increase in elongation at break of the composites based on PP matrix. Also, authors in [24] established that stearic acid favored the dispersion of PP/MMT nanocomposites when used as interface modifier and clay surface treatment.…”
Section: Imentioning
confidence: 94%
See 1 more Smart Citation
“…Zaharri N. et al also 2 of 9 reported that the mechanical properties of zeolite/propylene composite in the presence of stearic acid coupling agent was better than without stearic acid [14]. Angle et al found that the elongation at break of the composites containing modified bentonite increased, and the dispersion of bentonite was better in comparison with those containing unmodified bentonite [11]. Therefore, the aim of this study is to evaluate the dispersibility of stearic acid modified and unmodified inorganic fillers (bentonite, silica) in PE matrix.…”
Section: Introductionmentioning
confidence: 97%
“…However, due to the hydrophilic nature of these additives, it is necessary to treat their chemical surfaces before mixing them to increase their compatibility and dispersion into the PE matrix. To create the hydrophobic surface with the aim of increasing the compatibility of fillers with polymer molecules, fatty acids, such as oleic acid, stearic, palm oil [10][11][12] are often used. Stearic acid is most commonly used because of its advantages such as low cost and easy processing.…”
Section: Introductionmentioning
confidence: 99%